PROSEDUR PERMOHONAN GANTI NAMA DI PENGADILAN NEGERI YOGYAKARTA - , ELLY CAHYAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Adults often encounter a desire for changing their given name as it is too long and as such represents a burdensome. Therefore, a person who wants to change his/her name must do so by applying at the Local Court because the state has set up procedures for changing a name. A birth certificate is a legal document that must be changed as per District Court law article 52 No. 23 of 2006 regarding the administration of residence. This internship program adds to the experience and knowledge for technical writers and technical administration of justice within Yogyakarta court in order to become a professional. A request to change a name requires a decision by the district court where the applicant resides then the official copy of the decision is handed over to the Residents and Civil records (that include birth certificates) where courtâs decision is written at the back of the birth certificate